Progesterone analogues reduce plasma Epstein–Barr virus DNA load and improve pain control in recurrent/metastatic nasopharyngeal carcinoma patients under supportive care - Hung, Chia-Yen (Biomed J, 2017)
BACKGROUND: Progesterone analogues, such as megestrol acetate (MA) and medroxyprogesterone (MPA), have been used for the palliative care of cancer cachexia for decades and have proven to increase body weight and improve quality of life and performance status. The objective of this study was to determine the effect of progesterone analogue use on quality of life in terms of pain control, performance status, body weight gain, and Epstein–Barr virus (EBV) DNA load in recurrent/metastatic nasopharyngeal carcinoma (NPC) patients. METHODS: We retrospectively enrolled 41 patients with locally recurrent or metastatic NPC who received MA or MPA for cachexia management between January 2007 and February 2014. Patients who underwent aggressive treatment with intravenous chemotherapy were excluded. Body weight, performance status, pain score, and plasma EBV DNA load were used to assess quality of life before and after MA/MPA treatment. RESULTS: Of the 41 patients, 33 patients (80.5%) experienced body weight gain after progesterone analogue intervention. A significant reduction in plasma EBV DNA load was noted after progesterone analogue use (p < 0.001). In addition, median pain and Karnofsky performance scores were also significantly improved in progesterone analogue responders compared with non-responders (4 vs. 1 and 70 vs. 80, respectively; p = 0.004 and p < 0.001, respectively). CONCLUSION: Progesterone analogues improve quality of life in terms of performance status, pain control, and plasma EBV DNA load in patients with locally recurrent/metastatic NPC under palliative care.